2009
DOI: 10.1111/j.1740-8261.2009.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Appearance of Jejunal Lymph Nodes in Dogs Without Clinical Signs of Gastrointestinal Disease

Abstract: The jejunal lymph nodes of 57 dogs without clinical signs of gastrointestinal disease were examined to characterize their ultrasonographic appearance on B-mode and power Doppler examination, and to obtain ultrasonographic measurements. The lymph nodes were mildly hypoechoic to the mesentery in 71% of dogs and isoechoic in 29%. All dogs, 6 years of age or older had jejunal lymph nodes of uniform echogenicity. In dogs less than 6 years of age, nonuniform lymph nodes with different echopatterns were observed. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
32
7
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 29 publications
(74 reference statements)
19
32
7
4
Order By: Relevance
“…In this study, we used one transverse measurement on the short axis image (width) and two measurements on the long axis image (length and thickness). In contrast to previous studies (Agthe et al 2009), the width and thickness of jejunal lymph nodes were not directly related to growth in any of the sizes evaluated; rather, we found that the length of the jejunal lymph node was directly related to growth in large breed dogs and decreased in small breed dogs only. However, in that study, length was not measured, and the dogs belonged to a variety of breeds and were aged between six months and 14 years.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In this study, we used one transverse measurement on the short axis image (width) and two measurements on the long axis image (length and thickness). In contrast to previous studies (Agthe et al 2009), the width and thickness of jejunal lymph nodes were not directly related to growth in any of the sizes evaluated; rather, we found that the length of the jejunal lymph node was directly related to growth in large breed dogs and decreased in small breed dogs only. However, in that study, length was not measured, and the dogs belonged to a variety of breeds and were aged between six months and 14 years.…”
Section: Discussioncontrasting
confidence: 56%
“…During the time interval of evaluation, we found an increase in length of jejunal nodes in large-sized puppies and dimensions of iliac lymph nodes directly correlated with body weight in puppies of all three sizes. This is similar to previous studies of jejunal lymph nodes (Agthe et al 2009) and retropharyngeal lymph nodes (Burns et al 2008) but it is in contrast with other data (Stander et al 2010). It must be emphasised that these authors took only one measurement (thickness).…”
Section: Discussioncontrasting
confidence: 53%
“…The identification of medial iliac lymph nodes in healthy dog ranges from 45 per cent to 100 per cent (Llabrés-Díaz 2004, Mayer and others 2010). In another study, at least one jejunal lymph node was identified in 57/57 dogs, but gas-filled intestinal loops prevented the complete US assessment in three dogs during the first examination (Agthe and others 2009). In the authors’ institution, abdominal lymph node regions (coeliac, cranial mesenteric, lumbar and iliosacral lymphocenters) are usually inspected, and at least iliosacral and cranial mesenteric lymph nodes are consistently visualised during a complete abdominal US.…”
Section: Discussionmentioning
confidence: 98%
“…Lymph nodes may have either a homogeneous hypoechoic or isoechoic pattern, or a corticomedullary distinction with a hypoechoic rim surrounding the hyperechoic central rim, or a heterogenous aspect with a hypoechoic nodule (Nyman and O'Brien 2007, Agthe and others 2009, Mayer and others 2010, Stander and others 2010, Krol and O'Brien 2012). Many different ultrasonographic features have been studied to differentiate benign from malignant lymph nodes.…”
mentioning
confidence: 99%
“…Отсутствие в правом нижнем квадранте живота трубчатой структуры со слепым концом и усиленным кровотоком также свидетельствует в пользу ОНМЛ [44]. Диагностическая ценность УЗИ может сни-жаться у больных, госпитализируемых по экстренным показаниям, из-за отсутствия целенаправленной подго-товки кишечника [47,48].…”
Section: классификацияunclassified